Chironomidae (Diptera) en cursos de agua de Puna y Chaco Serrano de Catamarca (Argentina): primeros registros y distribución de géneros y especies - Rodríguez Garay, Gretel (2015)
The distribution in South America (Neotropical Region) of Stictocladius prati Saether & Cranston, Podonomus regalis Brundin, and P. setosus Brundin is enlarged as a result of new records from Argentina. Podonomus fastigians Brundin and Allocladius quadrus Andersen et al. are first recorded from Catamarca. The pupal type of Barbadocladius sp. “Chaco” (near B. andinus Cranston & Krosh) is described. Environmental variables in the sites where the species were collected are incorporated. Punean rivers presented alkaline waters and pH (8.12-8.8), high conductivity and organic matter (OM) content. The Chaco Serrano stream presented slightly alkaline waters, pH (7), low conductivity and OM content. The species Stictocladius prati, Allocladius quadrus, Podonomus fastigians P. setosus and P.regalis were present at high altitude rivers, alkaline waters and high conductivity while Barbadocladius sp. “Chaco” was sampled at a low altitude stream, with less alkaline and low conductivity waters.